Analysis of the clinicopathological characteristics and prognosis of triple-positive breast cancer and HER2-positive breast cancer—A retrospective study - Ma, Dongxu; Yang, Qing; Yin, Ke; Shi, Peng; Chen, Xiao; Dong, Tianyi; Shang, Xingchen; Tian, Xingsong (Frontiers in Oncology, 2023)
Background Adjuvant chemotherapy and targeted therapy have become standard postoperative therapeutic modalities for human epidermal growth factor receptor 2 (HER2)-positive breast cancer(HER2-positive,HR-negative), including triple-positive breast cancer(HER2-positive,HR-positive). However, these two types of breast cancer differ in terms of pathogenesis. This article analyzes these two types of breast cancer by comparing their prognoses. Methods The clinicopathological characteristics of 135 patients, including 60 patients with triple-positive breast cancer and 75 patients with HER2-positive breast cancer, were analyzed to compare the disease-free survival (DFS) and overall survival (OS) of the two groups over a 5-year period. A multifactorial Cox risk model was constructed by grouping age, menstrual status, maximum tumor diameter, number of lymph node metastases, pathological staging, and Ki-67 staining results. All statistical data were analyzed in detail using SPSS25.0 statistical software. Results The 5-year OS rates of patients with breast cancer in the triple-positive and HER2-positive groups were 96.7% and 82.7%, respectively, and the 5-year DFS rates were 90% and 73.3%, respectively. The Cox results revealed that molecular staging was an independent factor affecting recurrent metastasis and survival of breast cancer patients (hazard ratio [HR] =2.199, 95% confidence interval [CI], 1.296-8.266; HR = 9.994, 95% CI, 2.019-49.465). Conclusion The 5-year DFS and OS rates were significantly better in the triple-positive group than in the HER2-positive group. Subgroups received different prognosis for different chemotherapy regimens. Breast cancer patients should be treated according to the risk of recurrence with symptomatic treatment and precise regulation.